Konseling Eklektik Islami untuk Mengubah Konsep Diri Waria - Sutarto, Sutarto; Syafriyadin, Syafriyadin; Warlizasusi, Jumira (Universitas Islam Negeri Raden Intan Lampung, 2019)
This study aims to reveal the self-concept of transvestites, provide assistance for eclectic Islamic counseling services and know the effectiveness of Islamic eclectic counseling to change the self-concept of transvestites. The type of research used is Participatory Action Resarch (PAR) with four stages of implementation, namely planning, action, assessment and follow-up. The results of the study indicate that transvestites in understanding their own concepts can be grouped into two, namely; First, transvestites who see themselves as women and that are already destiny. Second, transvestites who see themselves as men but look like women. Transvestites assume that the community views itself as a woman, must appear like a woman and the community sees one eye towards her. Of the 18 transgender people who participated in the counseling process 1 person was determined to really want to change his appearance. 10 people are aware that they are men and their appearance should be like men but do not know when they will change their appearance and 7 people still understand themselves as women and must appear as a woman